Precoded multiuser distributed MIMO OFDM systems - Holakouei, R.
In this paper, we consider a multiuser distributed MIMO system, under multipath fading channels, with orthogonal frequency division multiplexing (OFDM) technology. The aim is to extend and evaluate, co-located precoding schemes that have been recently proposed, in a distributed scenario. Assuming knowledge of CSI prior to transmission, we can remove the interference among users by employing precoding schemes for the downlink. We assessed closed form and iterative schemes based on block diagonalization (BD) to improve the performance of the distributed antenna system. The results show that the iterative scheme outperforms the closed one. The simulation results show that the studied schemes can be efficient for distributed MIMO OFDM based systems.